Perancangan Prototipe Sistem Penerimaan Mahasiswa Baru (SPMB) Berbasis Web Menggunakan PHP dan Tailwind CSS Studi Kasus: Universitas Pamulang - Muhammad Yunus Rangkuti; Egia Eka Putra; Muhammad Akif Farhat; Muhammad Fatih Iqbal (shofanah Media Berkah, 2026)
The new student admission process serves as the main gateway to higher education institutions, requiring a modern system that is efficient, transparent, and easy to use. This research aims to design a new SPMB prototype that integrates CBT features, biodata management, and real-time graduation announcements. The development approach used is the Waterfall model, with implementation through the PHP programming language and Tailwind CSS framework to create a responsive interface. Results indicate that applying a utility-first interface significantly improves user experience (UX) for prospective students throughout registration and selection exams. Furthermore, the prototype includes an automated scoring algorithm that facilitates efficient academic graduation decisions.